Effect of TRAF6 in acute pancreatitis-induced intestinal barrier injury via TLR4/NF-κB signal pathway. (June 2022) - Wei, Biwei; Wu, Qing; Yang, Xuexia; Lai, Chen; Su, Zhou; Liang, Zhihai
Abstract: Background: The aim of this study was to investigate the effect of tumor necrosis factor receptor-related factor 6 (TRAF6) in acute pancreatitis (AP)-induced intestinal barrier injury via the Toll-like receptor 4/nuclear factor kappa-B (TLR4/NF-κB) signal pathway. Methods: Rat models of acute edematous pancreatitis (AEP) and acute necrotizing pancreatitis (ANP) were established by intraperitoneal injection of caerulein and retrograde infusion of sodium taurocholate solution into the biliopancreatic duct, respectively. Separate groups of model rats were pretreated with the TRAF6 inhibitor, MG-132. Rats were sacrificed at 12 h after the last injection for inducing AP. Histopathological changes, inflammatory response, intestinal barrier function, and protein expression levels were assessed by pathological score, ELISA, TUNEL, qRT-PCR, immunohistochemistry and western blotting. Results: Rat models of AEP and ANP were successfully established as evidenced by the pathological changes in the pancreas and intestine. Pre-treatment with MG-132 significantly alleviated pancreatic and intestinal pathological scores, reduced serum levels of amylase, IL-1β, and IL-6, and ameliorated apoptosis of mucosal cells. MG-132 reduced intestinal barrier injury, including serum levels of diamine oxidase and lipopolysaccharide, and intestinal expressions of ZO-1 and occludin. Moreover, it significantly suppressed the activation of the intestinal TLR4/NF-κB signaling pathway. Conclusions: TRAF6 inhibitor alleviated pancreatic and intestinal injury in AEP and ANP. This effect may be mediated through inhibition of the TLR4/NF-κB signaling pathway, which in turn regulates the inflammatory response and intestinal barrier injury. Highlights: Acute pancreatitis can cause intestinal barrier injury which related to inflammatory response. TLR4/NF-κB pathway participate in the mechanism of acute pancreatitis-induced intestinal barrier injury. TRAF6 inhibitor alleviated pancreatic and intestinal injury in acute pancreatitis via TLR4/NF-κB pathway.